Deletion of Plasmodium falciparum Protein RON3 Affects the Functional Translocation of Exported Proteins and Glucose Uptake - Leanne M. Low (American Society for Microbiology, 2019)
ABSTRACT The survival of Plasmodium spp. within the host red blood cell (RBC) depends on the function of a membrane protein complex, termed the Plasmodium translocon of exported proteins (PTEX), that exports certain parasite proteins, collectively referred to as the exportome, across the parasitophorous vacuolar membrane (PVM) that encases the parasite in the host RBC cytoplasm. The core of PTEX consists of three proteins: EXP2, PTEX150, and the HSP101 ATPase; of these three proteins, only EXP2 is a membrane protein. Studying the PTEX-dependent transport of members of the exportome, we discovered that exported proteins, such as ring-infected erythrocyte surface antigen (RESA), failed to be transported in parasites in which the parasite rhoptry protein RON3 was conditionally disrupted. RON3-deficient parasites also failed to develop beyond the ring stage, and glucose uptake was significantly decreased. These findings provide evidence that RON3 influences two translocation functions, namely, transport of the parasite exportome through PTEX and the transport of glucose from the RBC cytoplasm to the parasitophorous vacuolar (PV) space where it can enter the parasite via the hexose transporter (HT) in the parasite plasma membrane. IMPORTANCE The malarial parasite within the erythrocyte is surrounded by two membranes. Plasmodium translocon of exported proteins (PTEX) in the parasite vacuolar membrane critically transports proteins from the parasite to the erythrocytic cytosol and membrane to create protein infrastructure important for virulence. The components of PTEX are stored within the dense granule, which is secreted from the parasite during invasion. We now describe a protein, RON3, from another invasion organelle, the rhoptry, that is also secreted during invasion. We find that RON3 is required for the protein transport function of the PTEX and for glucose transport from the RBC cytoplasm to the parasite, a function thought to be mediated by PTEX component EXP2.